A 12-month, Open Label, Multicenter Pilot Study Evaluating Fingolimod Treatment in terms of Patient Satisfaction in Relapsing Remitting Multiple Sclerosis Patients FINE Trial - (:unkn) unknown (AVES, 2017)
Introduction: To assess satisfaction and quality of life in patients with relapsing-remitting multiple sclerosis (RRMS) who were receiving fingolimod (0.5 mg/day) for 12 months as a second-line treatment after switching from injectable agents. Methods: Patients aged 18-65 years with RRMS who fulfilled the eligibility criteria were enrolled from 16 centers throughout Turkey. Treatment Satisfaction Questionnaire for Medication and 36-item Short-Form Health Survey were completed at baseline and four visits to assess patient satisfaction and quality of life. Results: Forty-two patients (62% male; mean age: 35.7 +/- 9.4 years) were eligible for inclusion. Patient satisfaction scores at the end of the study 44.7 +/- 9.9) were significantly higher than those at baseline [32.0 +/- 9.9; (p<0.001)]. The only significant increase in the quality of life survey was in the emotional aspect (p=0.019). There were 124 adverse events and none of the five serious adverse events noted was considered drugrelated. Conclusion: Large-scale comparative studies performed with disease specific quality of life instruments will allow more information on this issue.
Keywords: Multiple sclerosis; fingolimod; patient satisfaction; quality of life; ORAL FINGOLIMOD; INTRAMUSCULAR INTERFERON; DOUBLE-BLIND; SAFETY; THERAPIES; EFFICACY; OUTCOMES; ACETATE; PHASE-3; SWITCH